The Communications Strategy of Halal Tourism Accelartion in Bandung Regency - Perbawasar, Susie; Sjuchro, Dian Wardiana; Setianti, Yanti; Nugraha, Aat Ruchiat; Juddi, Moh. Faidol (International Journal of Psychosocial Rehabilitation, 2020)
The rapid economic growth of Muslims in the world recently has made travelling as a new form of lifestyle. The emerging of this new lifestyle has also made most of the tourism countries around the globe to become more competitive in winning this sector of the industry. Indonesia, as one of the Muslim countries in the world, has successfully gained the top position for the halal tourism industry. This success has also made our Government focusing on building ten primary regions of halal tourism destinations, and one of those regions is The West Java Province with Bandung Regency as the priority. Bandung Regency must put its best efforts for the halal tourism program acceleration because the foreigner tourist visits especially the tourists from the middle-eastern as the priority are still very low. This acceleration effort needs the appropriate communication strategy. The form of communication approach carried out by the Bandung Regency government is top-down, and the Government as the main character. Bandung Regency government needs to rearrange the socialization strategy used because there is still a misconception among the stakeholders regarding the concept and standard of this halal tourism implementation. This rearrangement is regarding who is delivering the message, what is the message content to be provided, media selection, mapping of targeted communicants, and the expected effects. The communication approach should be more as "bottom-up" along with the community participation as the characteristic.